Evaluation of Prophylactic Antibiotic Use in The Surgical Action of Urinary Tract in Siloam Hospital Bali from January-June 2019 - Dewi, Fransiska (Brawijaya University, 2024)
Inappropriate use of antibiotics raises various problems to health, especially bacterial resistance to antibiotics. One of them is surgery with prophylactic antibiotics. The purpose of this study is to observe the accuracy of the usage of antibiotics in the surgical action of urinary tract. The method used is descriptive method with retrospective data collection from January to June 2019. The analyses used are the Gyssens method and the 2016 Indonesian Ministry of Health Guidelines for Antibiotics Usage. The biggest patient profile are aged 41-50 years (51 patients-43%), with 80% male and 20% female patients. Prophylactic antibiotics used for urinary tract surgical action is third-generation cephalosporin; cefoperazone (85%), cefotaxime (10%) and ceftriaxone (5%). Gyssens method is used to gain evaluation result; IVA Category (100%) and I Category (99,92%). Evaluation using the 2011 Ministry of Health method, namely accurate patient 100%, accurate doses 100%, and time of prophylactic antibiotics is 100%. Keywords: antibiotics, antibiotics rationality, Gyssens method.